Viral Kinetics in Sylvatic Yellow Fever Cases. (1st November 2022) - Avelino-Silva, Vivian I; Thomazella, Mateus Vailant; Marmorato, Mariana Prado; Correia, Carolina A; Dias, Juliana Z C; Maestri, Alvino; Cerqueira, Natalia B; Moreira, Carlos H V; Buccheri, Renata; Félix, Alvina C; Zanella, Luiz G F A B E; Costa, Priscilla R; et al.
Abstract: Background: Yellow fever is a mosquito-borne zoonotic disease caused by yellow fever virus (YFV). Between 2017 and 2019, more than 504 human cases and 176 deaths were confirmed in the outskirts of São Paulo city. Throughout this outbreak, studies suggested a potential association between YFV viremia and mortality. Methods: Viral ribonucleic acid was measured using reverse-transcription quantitative polymerase chain reaction in plasma samples collected at up to 5 time points, between 3 and 120 days after symptoms onset. Results: Eighty-four patients with confirmed YFV infection were included. Most were males, median age was 42, and 30 (36%) died. Deceased patients were older than survivors ( P = .003) and had a higher viremia across all time points ( P = .0006). Mean values of viremia had a positive, statistically significant correlation with peak values of neutrophils, indirect bilirubin, aspartate transaminase, international normalized ratio, and creatinine. Finally, a Cox proportional hazards model adjusted for age and laboratory variables showed that viremia is independently associated with death, with a mean 1.84-fold increase (84%) in the hazard of death ( P < .001) for each unit increase in mean log10 viremia. Conclusions: Our results raise the importance of monitoring YFV viremia and suggest a potential benefit of antiviral drugs or neutralizing monoclonal antibodies early in the course of this infection to improve disease outcomes. Abstract : Yellow fever virus viral load was found to be independently associated with mortality, showing the importance of monitoring viremia and suggesting it as a target to improve disease outcome of an endemic disease with high lethality rate in Brazil.